1992
DOI: 10.1007/bf00175933
|View full text |Cite
|
Sign up to set email alerts
|

Bullous retinal detachment and multiple retinal pigment epithelial detachments in patients receiving hemodialysis

Abstract: Two patients receiving hemodialysis for chronic renal failure developed bilateral bullous retinal detachment associated with multiple underlying serous detachments of the pigment epithelium. Many of the detachments of the pigment epithelium were surrounded by subretinal whitish exudate that was probably fibrinous in type. There was fluorescein angiographic evidence of dehiscence of the pigment epithelium at the margin of some of the pigment epithelial detachments. Failure to recognize the nature of the retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…Previous studies have shown an association between retinal disease and retinal or cardiac transplantation with the bullous variant of CSC [24, 25]. Corticosteroids also have been implicated in the pathogenesis of bullous retinal detachment [7, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an association between retinal disease and retinal or cardiac transplantation with the bullous variant of CSC [24, 25]. Corticosteroids also have been implicated in the pathogenesis of bullous retinal detachment [7, 26].…”
Section: Discussionmentioning
confidence: 99%
“…The association between having ESRD while on dialysis and serous retinal detachment has been reported by several studies [22–26]. Goldstein presented a case report where a patient with chronic renal failure developed into bullous serous retinal detachment and informed ophthalmologists and nephrologists the possibility of bullous serous retinal detachment [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism of the association between ESRD while on dialysis and serous retinal detachment has been controversial. Gass suggested that renal failure plays a more important role than dialysis in the pathophysiology of serous retinal detachment [22]. Because the fibrinous exudates were found beneath the margins of the dehiscent pigment epithelium and surrounding sub-retinal space, Gass hypothesized that large molecules, like fibrinogen, could enter the sub-retinal space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations